BULLDOZERS (Mankato, Minnesota : Creative Education and Creative Paperbacks, 2018)
A basic exploration of the parts, variations, and worksites of bulldozers, the leveling and scraping machines. Also included is a pictorial diagram of variations of bulldozers.
Includes index
Keywords: Bulldozers -- Juvenile literature; Earthmoving -- Juvenile literature